Daya Serap Lulusan Program Studi Ekonomi Keuangan Islam Pendekatan Alignment Index dan Exploratory - Nurul Huda; Nova Rini; Desti Anggraini; Khamim Hudori; Yosi Mardoni (TSAQAFAH, 2016)
The needs of human resource for the Islamic finance industry continues to increase along with the growth of the Islamic finance industry. The appearances of Department Economics and Islamic Finance have sprung due to meet the needs of the human resources, but a lot of graduates of the Department Economics and Islamic Finance did not accepted in the Islamic finance industries. This study was conducted to determine the absorption of graduates of the Department Economics and Islamic Finance, and the perception of the management of the Department Economics and Islamic Finance, and perception of Islamic finance practitioners of human resources with the approach of Alignment Index (AI) and exploratory. Human resources in the Islamic financial industry to apply the philosophy of ihsân at work. Philosophy of ihsan make human resources in Islamic finance industry becomes a subject not an object in the company’s operations so that a positive impact on the work environment that can increase the performance of the company or the Islamic finance industry. The results showed absorption graduates of the Department Economics and Islamic finance to Islamic finance industry in Sumatra below 40%. There is a difference in perception between the Islamic financial industry practitioners with management of the Department Economics and Islamic Finance about human resource. Practitioners of Islamic finance industry has a perception that human resource of Islamic financial institutions must have high competence, good soft skills and hard skills. The Department of Economics and Islamic Finance have the perception regarding human resources focus to understand the hard skills.